The changing incidence of childhood epilepsy in Finland - Sillanpää, Matti L. (Elsevier, 2025)
Introduction: to investigate the childhood epilepsy incidence, population trends, associated factors, and validate the national population registers.
Methods: a comprehensive comparative analysis of childhood epilepsy in the population during two distinct time intervals using medical records, appropriate national medical and population registers, and two random samples for control.
Results: In 1961-1964, the average incidence of epilepsy was 38/100,000 and during 1991-2000 65.9 (95 % CI 59.6 to 72.2) and 65.6/100,000 person-years after adjustment for the European Standard Population. This increase was significant (p<0.0001) as was a decline (p<0.003) from 1991 to 1995 to 1996-2000. The decline in incidence for girls occurred at a younger age compared to boys. Epilepsy cases associated with prenatal and perinatal factors were 50 % lower in 1991-2000 than in 1961-1964, especially related to asphyxia, infections, pre-eclampsia, and imminent abortion. The national Register for Healthcare independently identified 94.5 % of relevant cases (University Hospital alone 81.2 %, and Drug Register alone 74.3 %).
Discussion: Over the past five decades, the incidence rate of childhood epilepsy has exhibited a dynamic pattern, with a notable increase until the 1990's, followed by a stabilization at an incidence rate of approximately 60-70 per 100,000 person-years. Our findings, in line with other recent Finnish research, support a significant decrease in incidence since the mid-1990's. The underlying reasons for the increase and decrease remain unclear. Finnish national registers for epilepsy have established themselves as highly dependable resources for conducting epidemiological research.
Conclusion: Childhood epilepsy incidence in Finland is similar to other industrialized countries, but there are signs of a declining trend emerging.